READABILITY OF READING TEXTS IN ENGLISH TEXTBOOKS FOR THE TWELFTH GRADE STUDENTS - Iqbal, Muhammad; Dewi, Nora Ronita; Siregar, Masitowarni (Universitas Negeri Medan, 2019)
This study focused on the readability of reading texts in English textbooks for grade XII students in the academic year of 2018/2019 based on Dale and Chall formula. This study was categorized as descriptive qualitative research. The source of the data were 5 reading texts which consist of report, news item and procedure texts selected from English for Senior High School Students XII. The average readability score report texts in textbook was 6.9, while news item and procedure text in were 7.45 and 6.15. The scores indicated that the report text, news item and procedure text in English for Senior High School Students XII textbook were too easy for the twelfth grade students since the textbooks™ level was for the seventh and eighth grade.